Association Between Copper and Global Cognition and the Moderating Effect of Iron - Choe, Young Min; Suh, Guk-Hee; Lee, Boung Chul; Choi, Ihn-Geun; Lee, Jun Ho; Kim, Hyun Soo; Kim, Jee Wook (Frontiers in Aging Neuroscience, 2022)
Background: Despite the known association between abnormal serum copper levels and Alzheimer’s disease (AD) or cognitive decline, the association between copper, iron, and cognition remains poorly investigated. We examined the association between serum copper levels and global cognition measured using the Mini-Mental State Examination (MMSE) in older adults with normal copper levels. We also explored the moderating effect of iron on this association. Methods: The study enrolled 99 non-demented adults between 65 and 90 years of age. All the participants underwent comprehensive clinical assessments and serum copper measurements. Global cognitive performance was measured by the MMSE. All copper levels were within the normal range and were stratified into three categories: < 87 (low), 87 to 98 (medium), and > 98 (high: used as a reference category) µg/dL. Results: Serum copper level (as a continuous variable) was significantly associated with MMSE score (B = 0.065, 95% confidence interval = 0.023 to 0.108, p = 0.003). Low serum copper group showed significantly decreased MMSE score compared to high copper one (B = -2.643, 95% confidence interval = -4.169 to -1.117, p < 0.001), while middle copper category had no difference (B = -1.211, 95% confidence interval = -2.689 to 0.268, p = 0.107). There was a significant low serum copper × iron interaction effect on the MMSE score (B = 0.065, 95% confidence interval = 0.016 to 0.114, p = 0.010). Subgroup analyses showed that low serum copper was significantly associated with a low MMSE score in the low-iron (B = -4.174, 95% confidence interval = -6.607 to -1.741, p = 0.001) but not high-iron subgroup (B = -0.721, 95% confidence interval = -2.852 to 1.409, p = 0.495). Conclusions: Our findings from non-demented older adults suggest that a low serum copper level within the normal range was associated with AD or cognitive decline and this is moderated by iron. To prevent AD or cognitive decline, clinicians need to pay attention to avoiding low serum copper and iron levels, even within the clinical normal range.